2022
DOI: 10.1029/2022je007258
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Map of Water in the Martian Regolith Observed by FREND Neutron Telescope Onboard ExoMars TGO

Abstract: Introduction Measuring Water Content in Marstian Regolith Through Neutron FluxWater in the upper meter of Martian regolith is found practically everywhere on the planet using remote neutron and gamma ray sensing methods. It is most abundant in the polar regions above 60° latitude, where its content measured as Water Equivalent Hydrogen is higher than 40 wt% (WEH is a measure of water in weight percent (wt%) that the subsurface material contains in case all hydrogen is attributed to water molecules, H 2 O). Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Permittivity values from the Moon can also be used as a reference to provide an estimate of the density, as the lunar layers are typically dry, and have been compared with measurements of samples brought back to Earth [39]. According to data derived from the FREND workgroup [40], the water content of the shallowest subsurface is apparently low, which allows us to handle this material as dry volcanic rocks.…”
Section: Methodsmentioning
confidence: 99%
“…Permittivity values from the Moon can also be used as a reference to provide an estimate of the density, as the lunar layers are typically dry, and have been compared with measurements of samples brought back to Earth [39]. According to data derived from the FREND workgroup [40], the water content of the shallowest subsurface is apparently low, which allows us to handle this material as dry volcanic rocks.…”
Section: Methodsmentioning
confidence: 99%
“…Brine stability modeling by Chevrier et al (2020) found subsurface brines to mostly be frozen at depths greater than the annual thermal skin depth of ∼1 m. Brines with low water activities (such as the Mg/Ca-perchlorate brines) can remain liquid and evaporation can occur, but evaporation rates are below 1 mm per Martian year, too low to contribute significant O 2 fluxes into the atmosphere. Within the top few meters of the surface, neutron measurements by the Mars Odyssey Neutron Spectrometer (MONS; Feldman et al 2004;Wilson et al 2018), the Curiosity Dynamic Albedo of Neutrons (DAN) (Mitrofanov et al 2014), and the Trace Gas Orbiter (TGO) Fine-Resolution Epithermal Neutron Detector (FREND; Malakhov et al 2022) also found less than 10 wt% water equivalent hydrogen (WEH) in the Gale crater region. With such low wt% WEH values, the volume of water contained in the top meter of the surface would be an order of magnitude too small to dissolve the required amount of O 2 .…”
Section: Brinesmentioning
confidence: 99%
“…The information on water distribution can be obtained from radar sounding data, but outside the polar ice caps, in low and middle latitudes, the neutron monitoring data serve as a main source. Long-term orbital measurements of the neutron flux induced by cosmic radiation showed the presence of hydrogen nuclei in the upper (1-2 m) layers of regolith, corresponding to a mass fraction of water from units of percent to 20-40% (see, e.g., Malakhov et al, 2022). To detect ice at equatorial latitudes is possible only in deep canyons (Mitrofanov et al, 2022a).…”
Section: Study Of the Abundance Of Water In The Surface Layermentioning
confidence: 99%